2009
DOI: 10.1007/s10753-009-9106-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Carbon Monoxide Ameliorates Collagen-induced Arthritis in Mice and Regulates the Articular Expression of IL-1β and MCP-1

Abstract: Carbon monoxide (CO), long considered a toxic gas, has recently been shown to mediate anti-inflammatory effects in various animal models. The aim of this study was to investigate whether the inhalation of CO ameliorated collagen-induced arthritis (CIA) in mice. CIA was induced in female DBA/1 mice by the injection of an anti-type II collagen antibody and lipopolysaccharide. The CO treatment group was exposed to CO gas at a concentration of 200 ppm in a closed cage starting on the day of the injection with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Furthermore, we have described recently that both SLE patients, as well as lupus-prone mice, show a decreased expression of HO-1 in peripheral blood monocytes [14,15]. During immune-mediated diseases, such as MS, type 1 diabetes, collagen induced arthritis (CIA) and organ transplant rejection, several immunoregulatory functions have been attributed to CO, which is an HO-1 product [16][17][18][19]. Along these lines, we have recently reported that CO exposure prevents both monocyte population expansion and the decline of regulatory T cells (T regs ) in hybrid FcgRIIb knock-out (KO) mice, which develop a mild lupus-like syndrome [15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have described recently that both SLE patients, as well as lupus-prone mice, show a decreased expression of HO-1 in peripheral blood monocytes [14,15]. During immune-mediated diseases, such as MS, type 1 diabetes, collagen induced arthritis (CIA) and organ transplant rejection, several immunoregulatory functions have been attributed to CO, which is an HO-1 product [16][17][18][19]. Along these lines, we have recently reported that CO exposure prevents both monocyte population expansion and the decline of regulatory T cells (T regs ) in hybrid FcgRIIb knock-out (KO) mice, which develop a mild lupus-like syndrome [15].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent evidence suggests that providing exogenous CO suppresses the inflammatory response associated with various disease states and conditions such as hyperoxia [10], organ transplantation, ischemia-reperfusion injury [11][12][13][14], and inflammation [15,16]. In intestinal inflammation, exogenous CO also reduces the severity of disease activity [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Potent therapeutic efficacies of CO have been demonstrated in experimental models of several conditions, including lung injuries [35], heart, hepatic and renal I-R injuries [19,36,37], as well as inflammation, including arthritis [38], supporting the new paradigm that CO at low concentrations functions as a signaling molecule that exerts significant cytoprotection and anti-inflammatory actions. Similar to what has been observed for the therapeutic effects of CO against various diseases, CO has been reported to mediate potent cytoprotective and anti-inflammatory effects in in vivo colitis models (table 1).…”
Section: Therapeutic Effects Of Co In Ibdmentioning
confidence: 99%